TOXICITY ANALYSIS OF CRAB SHELL CHITOSAN ARGINYLGLYCYLASPARTIC ACID SCAFFOLD MEMBRANE AND ITS EFFECT ON HUMAN DENTAL PULP CELL VIABILITY - Dewi, Tri Kurnia; Shabrina, Mauldina; Fatmasuniarti, Dewi; Amir, Lisa; Idrus, Erik (International Journal of Applied Pharmaceutics, 2018)
Objective: Crab shell chitosan is a biomaterial used for scaffolding. In Indonesia, Badan Tenaga Nuklir Nasional has made a crab shell chitosan arginylglycylaspartic acid (RGD) scaffold membrane. The purpose of adding RGD was to enhance cell attachment to the scaffold. The objective of this research is to analyze the toxicity of crab shell chitosan RGD scaffold membrane on human dental pulp cells and its effect on their viability Methods: Human dental pulp cells were cultured for 5Â days in Minimum Essential Medium Alpha (Î±-MEM) complete containing amphotericin B, penicillin, streptomycin, and fetal bovine serum. Then, the treatment group was exposed to crab shell chitosan RGD scaffold membrane and crab shell chitosan scaffold membrane incubated for 24 h. The toxicity of the crab shell chitosan RGD scaffold membrane was analyzed with a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Result: The result of this research is that crab shell chitosan RGD scaffold membrane did not decrease the percentage of viability of human dental pulp cells. Conclusion: It is concluded that crab shell chitosan RGD scaffold membrane does not have toxic effects on human dental pulp cells.